Effect of Proprioceptive Neuromuscular Facilitation and Myofascial Release for trigger points in Upper cross Syndrome- An Experimental study - Shivangi Dutta Jha; Shuaib Akhtar; Vajrala Krishna Reddy; Chhavi Kumar Sharma; Jyoti Sharma; Mohammad Sidiq (Revista Electronica de Veterinaria, 1970)
In today’s lifestyle, faulty postures lead to musculoskeletal changes causing symptoms like neck and upper back pain. Postures such as bent posture result in deformities like rounded shoulders, forward head posture, and restricted thoracic spine mobility. Upper Cross Syndrome (UCS) is characterized by an unbalanced posture, overactive pectoralis and trapezius muscles, and postural abnormalities with muscle tightness and weakness. These issues can be corrected through strengthening and stretching exercises. This study aimed to compare the effects of myofascial release (MFR) and proprioceptive neuromuscular facilitation (PNF) on individuals with UCS. A total of 112 subjects meeting inclusion criteria were divided into two groups. Group A received PNF and conventional physiotherapy exercises with a hot pack, while Group B received MFR and conventional physiotherapy exercises. Subjects aged 18 and above of all genders participated. Visual Analog Scale (VAS) and Neck Disability Index (NDI) were used as outcome measures for pretest and posttest evaluations. Assessments were conducted before treatment and after six weeks. Results showed a significant difference between pretest and posttest scores in both groups. A comparison of NDI and VAS post-scores between groups indicated that PNF demonstrated superior outcomes to MFR. In conclusion, the experimental group receiving PNF outperformed the control group, confirming PNF's greater effectiveness in managing UCS compared to MFR.